Memoria fértil. Crianza de la historia en Huachichocana - Verónica S. Lema; Francisco Pazzarelli (Nuevo mundo - Mundos Nuevos, 2015)
This paper traces the paths that led to some reflections on relations involving people and archaeological sites in Huachichocana (Tumbaya department, Jujuy, Argentina). They are part of a larger aim: to achieve an understanding of the local perspectives related to the ' past ' and ' history ' of the place, where relationships with sites are presented as a more other significant relationships that constitute memory and the local landscape. These relationships are defined mainly by the place occupied by families in the definition of spaces (houses, “puestos”, places ), their productive linkages in the context of annual mobility patterns , and the close relationship between them and other ' beings ' : hills , ponds , springs , ravines , mines, and , of course , archaeological sites. All these reflections lead us to consider as essential the relationships of “nurturing” (crianza), so common in the Andean symbolic languages, and also present in Huachichocana.